2013
DOI: 10.1371/journal.pone.0066172
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Chickens with SPI1-lon and SPI1-lon-fliC Mutant of Salmonella enterica Serovar Enteritidis

Abstract: The prevalence of Salmonella enterica serovar Enteritidis is gradually decreasing in poultry flocks in the EU, which may result in the demand for a vaccine that allows for the differentiation of vaccinated flocks from those infected by wild-type S. Enteritidis. In this study, we therefore constructed a (Salmonella Pathogenicity Island 1) SPI1-lon mutant with or without fliC encoding for S. Enteritidis flagellin. The combination of SPI1-lon mutations resulted in attenuated but immunogenic mutant suitable for or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“…In short, in our studies the nonmotile virulence-plasmid cured (fliD-, pSEVΔ) mutant did not only provide protection against organ invasion but also effectively reduced caecal colonisation and cloacal shedding of the highly virulent S. Enteritidis. In this respect our results were similar to those of Matulova et al (2013).…”
Section: Inhibition (%)supporting
confidence: 91%
See 2 more Smart Citations
“…In short, in our studies the nonmotile virulence-plasmid cured (fliD-, pSEVΔ) mutant did not only provide protection against organ invasion but also effectively reduced caecal colonisation and cloacal shedding of the highly virulent S. Enteritidis. In this respect our results were similar to those of Matulova et al (2013).…”
Section: Inhibition (%)supporting
confidence: 91%
“…A significant (P < 0.01) increase at 4 weeks post inoculation was detected in SE11-inoculated chickens as compared to those inoculated with the nonmotile-plasmidless (fliD-, pSEVΔ) mutant SEΔ155. The results indicated that the significant difference in the titre of anti-flagellin antibodies can be used as a negative marker for the differentiation of vaccinated groups from those infected with the wild-type strain, similarly as has been described for the S. Enteritidis fliC-mutant very recently (Methner et al, 2011b;Matulova et al, 2013).…”
Section: Inhibition (%)supporting
confidence: 58%
See 1 more Smart Citation
“…Salmonella Pathogenicity Island 1 and 2 (SPI-1 and SPI-2) encode for two T3SS that are used to inject virulence factors into host cells (Galan and Collmer, 1999;Galan 2001;Hensel, 2000;Hensel and Kuhle, 2004) and play an important role in Salmonella pathogenesis (Desin et al, 2009;Wisner et al, 2010). Immunization of chickens with a SPI-1 lon mutant vaccine strain (Lon protease is a negative regulator of SPI-1) resulted in lower levels of Salmonella Enteritidis in the internal organs as well as the cecal contents (Matulova et al, 2013b). Likewise, a Salmonella Enteritidis DhilADssrADfliG triple mutant vaccine strain that contains deletions in the SPI-1, SPI-2, and flagellar genes was effective in reducing the number of chickens that were positive for Salmonella Enteritidis postvaccination (De Cort et al, 2013).…”
Section: Nontyphoidal Salmonella Speciesmentioning
confidence: 99%
“…The effector proteins act to manipulate central host functions (Fass & Groisman, 2009;McGhie et al, 2009;Ramos-Morales, 2012). It was recently reported that the combination of SPI-1-lon and SPI-1-lon-fliC (flagellin) mutations of S. Enteritidis resulted in an attenuated but immunogenic mutant suitable for the oral immunization of poultry (Matulova et al, 2013). Meanwhile, we previously observed significant increases in the amount of S. Typhimurium LPS-specific secretory IgA (sIgA) in intestinal lavage fluid and in the number of S. Typhimurium LPS-specific sIgA-producing cells in lamina propria lymphocytes in mice following an oral immunization with CS2022 (Lon protease-deficient S. Typhimurium) or CS2007 (ClpP protease-deficient S. Typhimurium).…”
Section: Introductionmentioning
confidence: 99%